Method for synthesizing biomass-based carbon material through molten salt method coupling activation and application of biomass-based carbon material

By coupling the molten salt method with activation technology, a biomass-based carbon material with a high specific surface area and a hierarchical porous structure was prepared, which solved the limitations of the biochar preparation method in the prior art and the environmental pollution problems, and achieved high-performance supercapacitor electrode material.

CN119660737APending Publication Date: 2025-03-21SOUTHEAST UNIV

Patent Information

Application Number
CN202411796755.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing biochar preparation methods have limitations in morphology and performance control, and the chemical method uses a large number of chemical reagents to increase production costs and environmental pollution risks, making it difficult to accurately regulate the pore structure of the molten salt method.

Method used

Coupled with the molten salt process and activation technology, biomass-based carbon materials with high specific surface area and a hierarchical porous structure are prepared through pre-carbonization, molten salt calcination and multiple washing steps.

Benefits of technology

The electrochemical properties of carbon materials are improved, including high specific capacity, high rate performance and good cycle stability, making them suitable for supercapacitor electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660737A_ABST
    Figure CN119660737A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing a biomass-based carbon material by coupling activation through a molten salt method, which comprises the following steps: (1) crushing a biomass raw material into powder, and pre-carbonizing at high temperature in an inert atmosphere to obtain biochar; (2) mixing biochar, chlorate molten salt and an activating agent, and calcining at high temperature in an inert atmosphere to obtain a carbon material; and (3) washing the obtained carbon material with water, carrying out suction filtration after water washing, then carrying out acid washing, carrying out suction filtration after acid washing, then carrying out water washing until eluate is neutral, and then drying to obtain the biomass-based carbon material. The invention also discloses an application of the carbon material prepared by the method in preparation of a supercapacitor. The biomass-based capacitor carbon material prepared by the invention has a graded porous structure, micropores are beneficial to improving the surface adsorption capacity of ions, mesopores can provide more active sites and enhance the ionic conductivity, and macropores can provide a rapid substance transmission channel and reduce the mass transfer resistance; through an electrochemical performance test, when the material is used as a supercapacitor electrode material, the material has excellent capacity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synthesizing a biomass-based carbon material, and also relates to the application of the carbon material prepared by the method in preparing a supercapacitor. Background Art

[0002] As a new type of electrode material, biochar has attracted more and more attention due to its excellent electrochemical properties, environmental protection characteristics and wide source of raw materials. At present, the preparation methods of biochar mainly include physical methods and chemical methods. Among them, although physical methods (such as gasification and pyrolysis) can effectively convert biomass, they have certain limitations in the morphology and performance control of the products. Although chemical methods (such as chemical activation) can improve the pore structure of carbon materials, they often require the use of a large amount of chemical reagents, which increases production costs and environmental pollution risks.

[0003] As an emerging material synthesis technology, the molten salt method has gradually attracted the attention of researchers in recent years. This method promotes the rapid reaction of reactants through the high temperature environment of molten salt to form carbon materials with good structural characteristics. However, the preparation of carbon materials only through the molten salt method has a single pore-forming effect and it is difficult to accurately control the pore structure of the material. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for synthesizing biomass-based carbon materials. The method can greatly increase the specific surface area of ​​the carbon material and form a hierarchical porous structure by coupling the molten salt method with the activation technology, thereby improving its electrochemical performance (high specific capacity, high rate performance and good cycle stability) when used as a supercapacitor electrode material; another purpose of the present invention is to provide the application of the carbon material obtained by the above method in the preparation of supercapacitors.

[0005] Technical solution: The method for synthesizing biomass-based carbon materials according to the present invention comprises the following steps:

[0006] (1) The biomass raw material is crushed into powder and pre-carbonized at high temperature in an inert atmosphere to obtain biochar. This process can remove impurities such as moisture and tar in the biomass, facilitate the subsequent uniform mixing of biochar with salt and activator, and improve the reaction activity;

[0007] (2) mixing biochar, chloride molten salt and an activator, and calcining at a high temperature in an inert atmosphere to obtain a carbon material;

[0008] (3) The obtained carbon material is first washed with water, filtered and then acid washed, and then filtered and then washed with water again until the washing liquid is neutral, and then dried to obtain a biomass-based carbon material.

[0009] Wherein, in step (1), the biomass raw material used is macadamia nut shell, corn stalk or wheat stalk.

[0010] Wherein, in step (1), the pre-carbonization temperature is 300-500°C, the heating rate during the pre-carbonization process is 5-10°C / min, and the time is 2-3h.

[0011] Wherein, in step (2), the chloride molten salt is NaCl / KCl molten salt, and the chloride molten salt is obtained by uniformly mixing NaCl and KCl in a mass ratio of 1:1; and the activator is one of potassium hydroxide, sodium hydroxide, phosphoric acid or potassium oxalate.

[0012] The mass ratio of biochar, NaCl / KCl molten salt and potassium hydroxide is 1:3:0.5. The carbon material prepared under this ratio has a high specific surface area and microporosity, and thus has a high specific capacity; however, when the ratio of molten salt to activator is reduced, the pore-forming effect is insufficient, the specific surface area will be reduced, and if too much activator is added, the carbon skeleton will collapse, and the micropores will be connected to form mesopores or macropores, which will not utilize energy storage.

[0013] Wherein, in step (2), the calcination temperature is 700-800°C, the heating rate during the calcination process is 5-10°C / min, and the time is 2-3h.

[0014] Wherein, in step (3), the carbon material is washed with water for 0.5 to 1 h; and the acid wash time is 3 to 6 h.

[0015] The acid used for pickling is 1M hydrochloric acid solution.

[0016] Wherein, in step (3), the drying temperature is 80-85° C. and the drying time is 5-24 h.

[0017] The carbon material prepared by the above method is used in the preparation of supercapacitors.

[0018] The supercapacitor comprises a positive electrode, a negative electrode, a diaphragm and an electrolyte; the positive and negative electrode materials of the supercapacitor are both biomass-based carbon materials prepared by the above method.

[0019] Molten salt acts as a template during the pyrolysis of carbon materials, generating a large number of pores of different sizes inside the material, which is beneficial to the storage, transfer and desorption of electrolyte ions during its application as an electrode material. At the same time, molten salt helps to remove impurities such as ash in biomass raw materials, effectively improving the purity of the prepared carbon materials and improving the capacity and stability of the carbon materials. In addition, adding a small amount of potassium hydroxide activator during the molten salt pyrolysis process can further increase the specific surface area and capacity of the capacitive carbon material, thereby forming a hierarchical porous structure. Micropores are beneficial to improving the surface adsorption capacity of ions, mesopores can provide more active sites and enhance ion conductivity, and macropores can provide a fast material transfer channel and reduce mass transfer resistance, thereby improving its electrochemical performance when used as a supercapacitor electrode material.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the biomass-based capacitor carbon material prepared by the present invention has a hierarchical porous structure, the micropores are beneficial to the storage of electrolyte ions, and the capacity of the capacitor carbon is improved, while the mesopores are beneficial to the mass transfer process of the electrolyte inside the carbon material, and the ion conductivity is enhanced. The micropores, mesopores and macropores cooperate with each other to form a capacitor carbon with high capacity, high rate performance and long cycle life; when it is used as a supercapacitor electrode material, it has excellent capacity and cycle stability after electrochemical performance testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a flow chart of the synthesis process of the present invention;

[0022] Figure 2 This is a SEM image of the biomass-based capacitor carbon synthesized in Example 1;

[0023] Figure 3 This is a SEM image of the biomass-based capacitor carbon synthesized in Comparative Example 2;

[0024] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution diagram of the biomass-based capacitor carbon synthesized in Example 1;

[0025] Figure 5 The XRD spectrum of the biomass-based capacitor carbon synthesized in Example 1;

[0026] Figure 6 CV curves of supercapacitors assembled based on biomass-based capacitor carbon in Example 1 at different current densities;

[0027] Figure 7 The constant current charge and discharge curves of the supercapacitor assembled based on the biomass-based capacitor carbon in Example 1 at different current densities;

[0028] Figure 8The current density-specific capacitance curves of the supercapacitors assembled based on Example 1, Comparative Example 1 and Comparative Example 2;

[0029] Fig. 9 This is a long cycle performance diagram of the supercapacitor assembled based on the biomass-based capacitor carbon in Example 1. DETAILED DESCRIPTION

[0030] Example 1

[0031] like Figure 1 As shown, the method for synthesizing biomass-based carbon materials of the present invention comprises the following steps:

[0032] (1) Using a crusher, the biomass raw material was crushed into a powder of 100 mesh, and then kept in a tube furnace at 500° C. in an argon atmosphere for 2 h. After cooling to room temperature, the pre-carbonized biochar was taken out; the biomass raw material used in this embodiment was macadamia nut shell;

[0033] (2) Pre-carbonized biochar, NaCl / KCl molten salt (NaCl and KCl are uniformly mixed in a mass ratio of 1:1) and potassium hydroxide in a mass ratio of 1:3:0.5 are mixed and fully mixed by grinding, and then placed in a tube furnace at 800°C in an argon atmosphere for 2 hours, and the capacitor carbon material is taken out after cooling to room temperature;

[0034] (3) The calcined capacitor carbon material is washed with deionized water, placed in deionized water, and stirred on a magnetic stirrer for 1 hour to fully dissolve the molten salt and potassium hydroxide in the capacitor carbon material into the water, and then the capacitor carbon and the solution are separated by a suction filtration device, and the filtrate is placed in an oven at 100° C. and dried for 24 hours. After the water is evaporated, the residual molten salt is taken out and recycled in step (2) (the recovered mixture is the molten salt and the activator);

[0035] (4) The capacitor carbon material obtained by filtration in step (3) is acid-washed with a 1M hydrochloric acid solution. The capacitor carbon material is placed in a 1M hydrochloric acid solution and stirred on a magnetic stirrer for 5 hours to allow the impurities in the capacitor carbon material to be fully dissolved in the hydrochloric acid. After the stirring is completed, the capacitor carbon material is filtered using a suction filtration device. During the filtration process, deionized water is added to wash the capacitor carbon material until the washing liquid is neutral. The washed capacitor carbon material is then placed in an oven at 80° C. and dried for 24 hours. After the water in the capacitor carbon material is completely evaporated, the final target product is obtained.

[0036] The biomass-based capacitor carbon prepared in Example 1 was structurally characterized: the morphology of the capacitor carbon is as follows: Figure 2 As shown, it can be seen from the electron microscope image that under the action of molten salt and activator, a large number of disordered pore structures are formed inside the capacitor carbon, which is conducive to the transmission and storage of electrons and ions. Figure 4The nitrogen adsorption-desorption curve shows a type IV isotherm and a hysteresis loop, indicating that there are mesopores in the capacitor carbon. The high nitrogen adsorption at relative pressure P / P0<0.1 indicates that there are a large number of micropores in the capacitor carbon, showing a hierarchical porous carbon structure. The pore size distribution curve shows a peak at 2nm, indicating that there are not only a large number of micropores in the capacitor carbon, but also a considerable number of mesopores. Figure 5 The XRD spectrum shown shows two broad peaks at 24° and 44°, indicating that the carbon structure is disordered. A large number of carbon defects adsorb electrolyte ions on the electrode / electrolyte interface, which is conducive to the formation of double-layer capacitance; the peak at 24° clearly shows that the degree of graphitization of the capacitor carbon is high, and the thermal stability, conductivity and mechanical properties of the carbon material are improved.

[0037] Based on the biomass-based capacitor carbon assembled supercapacitor in Example 1, the positive and negative electrode materials of the double-layer supercapacitor are both the biomass-based capacitor carbon prepared in Example 1, and the preparation method of the supercapacitor is as follows:

[0038] (1) Preparation of electrodes: The electrode slurry consists of 80 wt.% of biomass-based capacitor carbon, 10 wt.% of acetylene black (conductive agent) and 10 wt.% of PVFD (binder) (mass ratio is 8:1:1); first, PVDF is fully dissolved in NMP solution, and then the biomass-based capacitor carbon and acetylene black that have been mixed evenly are added thereto, and the mixture is fully ground into a slurry using a mortar; the slurry is evenly coated on a copper foil using a coater, and then the electrode is dried in a vacuum oven at 80°C for 12 to 24 hours to obtain the positive and negative electrode materials of the supercapacitor.

[0039] (2) Assembly of supercapacitor: The negative electrode shell, spring, gasket, negative electrode sheet, diaphragm, positive electrode sheet and positive electrode shell are installed in order from bottom to top. During this period, 6M potassium hydroxide electrolyte is dripped onto the negative electrode sheet and diaphragm twice. Finally, the supercapacitor is pressed tightly using a button battery sealing machine. The assembly of the button supercapacitor is completed.

[0040] Electrochemical performance test of supercapacitor: Figure 6 Figure 2 shows the CV curves of supercapacitors at different scan rates. It can be seen that all CV curves are approximately rectangular, indicating that the capacity of the supercapacitor is mainly double-layer capacitance, and it has the characteristics of fast charging and discharging and low internal resistance. Figure 7 The constant current charge and discharge (GCD) curves of supercapacitors at different current densities are shown. It can be seen that the GCD curves are approximately isosceles trapezoids, that is, the charging and discharging times are roughly the same at the same current, indicating that the supercapacitor has a small polarization effect, low internal resistance, and small energy loss; at a larger current density, the GCD curve can still maintain an isosceles trapezoid shape, indicating that the supercapacitor has good stability and can adapt to rapid charging and discharging at various current densities. Figure 8 The specific capacity of the supercapacitor at different current densities is demonstrated. It can be seen that the specific capacity gradually decreases with the increase of current density. At a current density of 0.5A / g, the capacitor carbon material exhibits a high specific capacity of 385F / g. Fig. 9 It was demonstrated that the supercapacitor still maintained 93% of its capacity (capacity retention rate reached 93%) after 5000 cycles at a high current density of 20A / g, indicating that it has good cycle stability.

[0041] The biomass-based capacitor carbon material prepared by the present invention has a specific surface area of ​​1754.88m2 / g and a hierarchical porous structure, which is conducive to the adsorption, desorption and rapid transfer of electrolyte ions inside the material; by assembling into a double-layer supercapacitor for electrochemical performance testing, the capacity can reach 385F / g at a current density of 0.5A / g, and at a current density of 10A / g, an excellent rate performance of 235F / g can be achieved.

[0042] Comparative Example 1

[0043] A method for synthesizing a biomass-based carbon material comprises the following steps:

[0044] (1) Using a crusher, the biomass raw material was crushed into a powder of 100 mesh, and then kept in a tube furnace at 500° C. in an argon atmosphere for 2 h. After cooling to room temperature, the pre-carbonized biochar was taken out; the biomass raw material used in this embodiment was macadamia nut shell;

[0045] (2) The pre-carbonized biochar was placed in a tubular furnace and kept at 800°C in an argon atmosphere for 2 hours. After cooling to room temperature, the capacitive carbon material obtained after calcination was taken out.

[0046] A supercapacitor is assembled based on the biomass-based capacitor carbon in Comparative Example 1, and the positive and negative electrode materials of the double-layer supercapacitor are both the biomass-based capacitor carbon prepared in Comparative Example 1. The preparation method of the supercapacitor is the same as that in Example 1.

[0047] The supercapacitor was electrochemically tested and its specific capacitance at different current densities was as follows: Figure 8 As shown, compared with Example 1, the capacity of the supercapacitor has decreased significantly, indicating that the capacitor carbon material synthesized in Example 1 has the advantages of high capacity, stable cycle performance and good electrochemical performance when applied to supercapacitors.

[0048] Comparative Example 2

[0049] A method for synthesizing a biomass-based carbon material comprises the following steps:

[0050] (1) Using a crusher, the biomass raw material was crushed into a powder of 100 mesh, and then kept in a tube furnace at 500° C. in an argon atmosphere for 2 h. After cooling to room temperature, the pre-carbonized biochar was taken out; the biomass raw material used in this embodiment was macadamia nut shell;

[0051] (2) Pre-carbonized biochar and NaCl / KCl molten salt (NaCl and KCl are uniformly mixed in a mass ratio of 1:1) are mixed in a mass ratio of 1:3, and the mixture is fully mixed by grinding, and then placed in a tube furnace at 800°C in an argon atmosphere for 2 hours, and the capacitor carbon material is taken out after cooling to room temperature;

[0052] (3) The calcined capacitor carbon material is washed with deionized water, placed in deionized water, and stirred on a magnetic stirrer for 1 hour to fully dissolve the molten salt in the capacitor carbon material into the water, and then the capacitor carbon and the solution are separated by a suction filtration device, and the filtrate is placed in a 100° C. oven and dried for 24 hours. After the water is evaporated, the residual molten salt is taken out and recycled in step (2);

[0053] (4) The capacitor carbon material obtained by filtration in step (3) is acid-washed with a 1M hydrochloric acid solution. The capacitor carbon material is placed in a 1M hydrochloric acid solution and stirred on a magnetic stirrer for 5 hours to allow the impurities in the capacitor carbon material to be fully dissolved in the hydrochloric acid. After the stirring is completed, the capacitor carbon material is filtered using a suction filtration device. During the filtration process, deionized water is added to wash the capacitor carbon material until the washing liquid is neutral. The washed capacitor carbon material is then placed in an oven at 80° C. and dried for 24 hours. After the water in the capacitor carbon material is completely evaporated, the biomass-based capacitor carbon is obtained.

[0054] A supercapacitor is assembled based on the biomass-based capacitor carbon of Comparative Example 2, and the positive and negative electrode materials of the double-layer supercapacitor are both the biomass-based capacitor carbon prepared in Comparative Example 2. The preparation method of the supercapacitor is the same as that of Example 1.

[0055] Depend on Figure 3 It can be seen that the porosity of the carbon material prepared in Comparative Example 2 is significantly reduced; the supercapacitor assembled with this material is subjected to electrochemical testing. Figure 8 It is shown that the specific capacitance of the material at different current densities is significantly reduced compared with the material in Example 1.

Claims

1. A method for synthesizing biomass-based carbon materials by coupling activation with a molten salt method, characterized in that: The steps include: (1) crushing the biomass raw material into powder, and pre-carbonizing it at high temperature in an inert atmosphere to obtain biochar; (2) mixing biochar, chloride molten salt and an activator, and calcining at a high temperature in an inert atmosphere to obtain a carbon material; (3) The obtained carbon material is first washed with water, filtered and then acid washed, and then filtered and then washed with water again until the washing liquid is neutral, and then dried to obtain a biomass-based carbon material.

2. The method for synthesizing biomass-based carbon materials according to claim 1, characterized in that: In step (1), the pre-carbonization temperature is 300-500° C., the heating rate during the pre-carbonization process is 5-10° C. / min, and the pre-carbonization time is 2-3 h.

3. The method for synthesizing biomass-based carbon materials according to claim 1, characterized in that: In step (2), the chloride molten salt is NaCl / KCl molten salt; and the activator is one of potassium hydroxide, sodium hydroxide, phosphoric acid or potassium oxalate.

4. The method for synthesizing biomass-based carbon materials according to claim 3, characterized in that: The mass ratio of biochar, NaCl / KCl molten salt and potassium hydroxide is 1:3:0.

5.

5. The method for synthesizing biomass-based carbon materials according to claim 1, characterized in that: In step (2), the calcination temperature is 700-800° C., the heating rate during the calcination process is 5-10° C. / min, and the calcination time is 2-3 h.

6. The method for synthesizing biomass-based carbon materials according to claim 1, characterized in that: In step (3), the carbon material is washed with water for 0.5 to 1 h, and the acid wash time is 3 to 6 h.

7. The method for synthesizing biomass-based carbon materials according to claim 6, characterized in that: The acid used for pickling is 1M hydrochloric acid solution.

8. The method for synthesizing biomass-based carbon materials according to claim 1, characterized in that: In step (3), the drying temperature is 80 to 85° C. and the drying time is 5 to 24 hours.

9. Use of the carbon material obtained by the method according to claim 1 in preparing supercapacitors.

10. The use according to claim 9, characterized in that: The positive and negative electrode materials of the supercapacitor are both biomass-based carbon materials prepared by the above method.

Citation Information

Patent Citations

  • Preparation method of nitrogen-loaded self-templated active carbon electrode material for supercapacitor

    CN109887759A

  • Method for preparing supercapacitor carbon material by adopting bio-oil

    CN110028050A

  • Biomass porous carbon material and preparation method thereof

    CN110835107A

  • Method for preparing capacitor carbon by using chlorate as template agent and cyclically regenerating template agent

    CN113697807A

  • Process for Producing A Highly Activated, Monolithic Net-Shaped Biochar Electrode

    US20220169511A1

Cited By

  • Cotton sugar-based activated carbon as well as preparation method and application thereof

    CN120854180A